HYDROLOGICAL AND ENVIRONMENTAL CHARACTERISTICS OF WETLANDS IN EGYPT - Hossam M. Nagy (International Association of Lowland Technology, 2001)
Egyptian wetlands are classified into two broad categories: coastal adn inland wetlands. The major problem of coastal wetlands, which are located in the northerm part of the Nile Delta, is the environmental impacts caused by the intrusion of saline water into fresh water aquifer. Inland wetlands, which are often located in the depressions of western desert or other areas along the Nile Valley, can be further classified as either natural wetland such as Wadi Elnatrun depression, or manmade wetland such as Siwa oasis. The associated problems in manmade wetlands comprise the groundwater abstraction which often exceeds the actual need, the negative impact of upland drainage on neighboring lowland, and the rise of groundwater table in agricultural lands due to illegal alteration of irrigation systems by farmers. Another type of manmade wetlands is the riverine land, which was existed in south of Egypt after the construction of Aswan High Dam and caused dramatic migration for some living societies and relocation of some historical monument. This review addresses the current problems faced by those coastal and inland wetlands, and illutrates the mitigation systems proposed in Egypt for tackling such problems.